Community Screening of Prostate Cancer in Eastern Nepal - Belbase, Narayan; Agrawal, C.S. (Nepalese Journal of Cancer, 2017)
Background: Prostate cancer incurs a substantial incidence and mortality burden, and it ranks among the top ten specific causes of death in males.Objectives: To explore the situation of prostate cancer in a cohort of healthy population in Eastern Nepal.Methods: This study was conducted in the Department of General surgery at B. P. Koirala Institute of Health Sciences, Dharan, Nepal in the department of surgery from July 2010 to June 2011. Males above 50 years visiting Surgical Outpatient Department in BPKIHS were enrolled in the study. Screening camps were organized in four Teaching district hospitals of BPKIHS in Eastern Nepal. Digital rectal examination (DRE) was done by the trained professionals after collecting blood for serum prostatic specific antigen (PSA). Trucut biopsy was done for all individuals with abnormal PSA, DRE or both findings.Results: A total of 1521 males more than 50 years of age were assessed and screened after meeting inclusion criteria. Maximum individuals 1452 (96.2% ) had PSA ≤ 4.0 ng/ml. Abnormal PSA ( > 4 ng/ml) was found in 58 (3.8%) individuals. Abnormal DRE was found in 26 (1.72%) individuals. Both DRE and PSA was abnormal in 26 (1.72%) individuals. On the basis of raised PSA or abnormal DRE 58 (3.84%) individuals were subjected to digitally guided trucut biopsy. Biopsy report revealed Benign Prostatic Hyperplasia in 47 (3.11%) individuals and adenocarcinoma prostate in 11 (0.73%) individuals. The specificity of DRE was 65.95% sensitivity 90.9% and positive predictive value 38.46%. The sensitivity of PSA more than 4ng/ml in detecting carcinoma prostate was 100% and the positive predictive value for serum PSA was 18.96%.Conclusion: The overall cancer detection rate in this study was 0.73% and those detected were locally advanced. Larger community-based studies are highly warranted specially among high-risk groups.